ANALISIS PERMOHONAN PAILIT TERHADAP PERSEROAN TERBATAS OLEH TENAGA KERJA (STUDI PUTUSAN PENGADILAN DALAM PERKARA ANTARA ROHANI,DKK MELAWAN PT. INDAH PONTJAN) - Manambus Pasaribu; Bismar Nasution; Sunarmi Sunarmi; Mahmul Siregar (Universitas Sumatera Utara, 2014)
ABSTRACT The result of this research show that Legally binding verdict of Industrial Dispute Settlement Court penalized employers to pay workers' basic rights / labor is debt in a broad sense. Legally binding verdict of Industrial Dispute Settlement Court but remains unimplemented can be submitted as the basis of request for bankruptcy and it is not a premature request as well as does not violate nebis in idem. Legal consideration of judges was appropriate based on the legal facts, definition of debt, the maturity of debt, the presence of two or more creditors and the implementation of simple evidentiary principle. Meanwhile, Supreme Court both in Cassation and the Reconsideration did not refer to the definition of debt in a broader sense, the debt has matured, the presence of two or more creditors and implementation of a simple evidence. Judges of the Supreme Court both in Cassation and Reconsideration was very subjective, tends to formality matters, as well as was not substantive in making of verdict.